2017
DOI: 10.3892/ol.2017.6765
|View full text |Cite
|
Sign up to set email alerts
|

Increased cell apoptosis in human lung adenocarcinoma and in vivo tumor growth inhibition by RBM10, a tumor suppressor gene

Abstract: Tumor suppressor genes are frequently deleted or mutated in lung cancer. The RNA-binding motif protein 10 (RBM10) gene has the ability to suppress tumor activity, but the role of RBM10 during the development of lung cancer has yet to be elucidated. The current study investigated the expression levels of RBM10 in non-tumor and tumor tissues obtained from patients with adenocarcinoma using reverse transcription-polymerase chain reaction and western blot analysis, and identified a reduction in RBM10 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The analyses of LUAD samples in TCGA indicate that RBM10 mutations may contribute to LUAD progression [32] and associate with a number of splicing changes [33] . Previous functional studies using lung cancer cell lines showed contradictory roles of RBM10 in LUAD progression [34] , [35] , [36] , [37] . Therefore, the exact function and underlying molecular mechanism of RBM10 in lung cancer remain to be determined.…”
Section: Introductionmentioning
confidence: 95%
“…The analyses of LUAD samples in TCGA indicate that RBM10 mutations may contribute to LUAD progression [32] and associate with a number of splicing changes [33] . Previous functional studies using lung cancer cell lines showed contradictory roles of RBM10 in LUAD progression [34] , [35] , [36] , [37] . Therefore, the exact function and underlying molecular mechanism of RBM10 in lung cancer remain to be determined.…”
Section: Introductionmentioning
confidence: 95%
“…RBM10, a tumor suppressor gene [28,29], encodes a nuclear protein that contains an RNArecognition motif. RBM10 regulates pre-mRNA splicing in the alternative splicing pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…RBM10, a tumor suppressor gene [28,29], encodes a nuclear protein that contains an RNA-recognition motif. RBM10 regulates pre-mRNA splicing in the alternative splicing pathway [30].…”
Section: Discussionmentioning
confidence: 99%